Experimental Investigation of the Influence of Gradation Parameters on Atterberg Limits of Soil - G. O. Adunoye; A. B. Badmus; S. A. Sagbele (Archives of Current Research International, 2018)
This study investigated the influence of gradation parameters on Atterberg Limits of soil. This was with a view to establishing a relationship between the two geotechnical properties. Disturbed soil samples were collected from selected locations. The natural moisture contents, grain size analysis and Atterberg Limits tests were conducted on the collected soil samples, following standard procedures. From the particle size analyses, effective sizes, sorting coefficients, coefficient of uniformity and coefficient of gradation were determined. Regression analysis was then used to investigate and establish relationships between gradation parameters and Atterberg Limits. The study concluded that gradation has effect on the Atterberg Limits of the selected soil samples. The developed model for Liquid Limit (LL = -5.88x10-1Cu2 + 3.71CuSo - 19.41So2 + 6.44Cu + 29.25So + 0.53) is the best model with R2 value of 0.95 and RSS (Residual Sum of Squares) value of 23.92.